Big Data-Driven Detection of False Data Injection Attacks in Smart Meters - Unal, Fatih; Almalaq, Abdulaziz; Ekici, Sami; Glauner, Patrick (Ieee-Inst Electrical Electronics Engineers Inc, 2021)
Today's energy resources are closer to consumers thanks to sustainable energy and advanced metering infrastructure (AMI), such as smart meters. Smart meters are controlled and manipulated through various interfaces in smart grids, such as cyber, physical and social interfaces. Recently, a large number of non-technical losses (NTLs) have been reported in smart grids worldwide. These are partially caused by false data injections (FDIs). Therefore, ensuring a secure communication medium and protected AMIs is critical to ensuring reliable power supply to consumers. In this paper, we propose a novel Big Data-driven solution that employs machine learning, deep learning and parallel computing techniques. We additionally obtained robust statistical features to detect the FDIs based cyber threats at the distribution level. The performance of the proposed model for NTL detection is investigated using private smart grid datasets in the Turkish distribution network for AMI-level cyber threats, and the results are compared to state-of-the-art machine learning algorithms used for NTL classification problems. Our approach shows promising results, as the accuracy, specificity, and precision metrics of most classifiers are above 90% and false positive rates vary between 0.005 to 0.027.
Keywords: Meters; Feature extraction; Smart meters; Big Data; Smart grids; Load modeling; Data models; Advanced metering infrastructure; big data; false data injection; feature extraction; machine learning; non-technical losses; smart meter